Maslinic acid ameliorates NMDA receptor blockade-induced schizophrenia-like behaviors in mice. (November 2017) - Jeon, Se Jin; Kim, Eunji; Lee, Jin Su; Oh, Hee Kyong; Zhang, Jiabao; Kwon, Yubeen; Jang, Dae Sik; Ryu, Jong Hoon
Abstract: Schizophrenia is a chronic psychotic disorder characterized by positive, negative, and cognitive symptoms. Primary treatments for schizophrenia relieve the positive symptoms but are less effective against the negative and cognitive symptoms. In the present study, we investigated whether maslinic acid, isolated from Syzygium aromaticum (clove), can ameliorate schizophrenia-like behaviors in mice induced by MK-801, an N-methyl-d -aspartate (NMDA) receptor antagonist. After maslinic acid treatment in the MK-801 model, we examined the behavioral alteration and signaling pathways in the prefrontal cortex. Mice were treated with maslinic acid (30 mg/kg), and their behaviors were evaluated through an array of behavioral tests. The effects of maslinic acid were also examined in the signaling pathways in the prefrontal cortex. A single administration of maslinic acid blocked the MK-801-induced hyperlocomotion and reversed the MK-801-induced sensorimotor gating deficit in the acoustic startle response test. In the social novelty preference test, maslinic acid ameliorated the social behavior deficits induced by MK-801. The MK-801-induced attention and recognition memory impairments were also alleviated by a single administration of maslinic acid. Furthermore, maslinic acid normalized the phosphorylation levels of Akt-GSK-3β and ERK-CREB in the prefrontal cortex. Overall, maslinic acid ameliorated the schizophrenia-like symptoms induced by MK-801, and these effects may be partly mediated through Akt-GSK-3β and ERK-CREB activation. These findings suggest that maslinic acid could be a candidate for the treatment of several symptoms of schizophrenia, including positive symptoms, sensorimotor gating disruption, social interaction deficits, and cognitive impairments. Highlights: NMDA receptor hypofunction induces behavioral problems like hyperactivity and abnormal social interaction and cognition. Maslinic acid normalized the MK-801-induced alterations in phosphorylation levels of Akt-GSK-3β and ERK-CREB in the PFC. Maslinic acid would be useful against NMDA receptor hypoactivity, such as schizophrenia.